Demand-driven vegetable breeding for impact - Barchenger, Derek; Zohoungbogbo, Herbaud; Ambali, Mwasilwa; Nalla, Manoj Kumar; Eybishitz, Assaf; Schreinemachers, Pepijn (CGIAR System Organization, 2024)
Pest and disease resistance and quality traits and preferences of the various stakeholders throughout the value chain are critically important for vegetables, even more so than yield. Vegetable breeders must consider all demands of users in order to develop and release vegetable varieties that will improve the livelihoods of smallholder farmers. For WorldVeg, this starts with extensive and close relationships with the private seed sector, who have the same goals as us. This is then validated through experiments to diagnose pests and diseases, visits to farmer fields and discussions with farmers and nursery owners, and interactions with the traders, exporters, and processors. Participatory variety selection is essential to our success, especially at the finished line stage prior to registration and release. Demand-driven breeding requires 360° feedback from users throughout the vegetable value chain and is essential to develop and release vegetable varieties that will be adopted by smallholder farmers.